Optimizing Instagram Promotion: A Netnographic Study on the Impact of Influencers and Paid Promotions in the Screen-Printing Business - Putriana, Rizqika Aulia; Sari, Dhany Efita (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The objective of this research is to describe the use of Instagram social media, the challenges in using influencer services and paid promotions as promotional media through Instagram, and the positive and negative impacts of using influencer services and paid promotions for promotional purposes through Instagram in the screen-printing business of Merv Industries. The type of research employed is qualitative research with a netnographic study design. Data validity is ensured through qualitative triangulation of sources and methods. The data collection techniques used include interviews, observation, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion and verification. The research findings indicate that Instagram has been established as one of the primary social media promotion platforms because it is a relatively easy step to introduce a brand using influencer services and paid promotions. The findings suggest that these promotional strategies have a significant positive impact on the business, helping to introduce its products to a broader network through promotional media, especially Instagram. The initial idea for choosing to use influencer services and paid promotions as a promotional medium involves selecting trending influencers, as they provide a good impact on the business, while paid promotions are primarily used to introduce the business. The positive impacts include an increase in followers, profile visits on Instagram, and gaining profits and popularity. The negative impact noted is the occurrence of negative comments. The proposed solution is to better select influencers and paid promotions that provide good feedback to increase sales, not just to introduce the brand. Future research could focus on the obstacles in selecting influencer services and paid promotions.